Relation between body mass index and serum aminotransferases concentrations in professional athletes - Banfi, G.; Morelli, P. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim: Reference intervals commonly used for evaluating and interpreting laboratory values obtained in athletes are the same used in the general population. Aminotransferases (aspartate aminotransferase [AST], and alanine aminotransferase [ALT]) are commonly analyzed in serum for evaluating hepatic function. Some studies in the general population and in blood donors testified that ALT concentrations clearly correlated with weight and body mass. Methods: We compared the aminotransferase concentrations at rest of 116 male professional athletes of 7 different sport disciplines with their body mass index (BMI). The blood drawing was performed before the start of training and of the competitive season. The athletes engaged in rugby, triathlon, soccer, sailing, cycling, basketball, alpine skiing. One hundred age-matched, apparently healthy, not physically active, males chosen for general check-up were recruited as a control group. Results: The average concentrations of AST and ALT in the whole group of athletes were 24.4 U/L (standard deviation [SD]: 10.5) and 23.6 (SD: 6.5). The results in athletes were not statistically different from those of sedentary people. A positive correlation between BMI and ALT exists, whilst a very weak negative correlation between BMI and AST occurs. Conclusion: High concentrations of ALT should be evaluated considering BMI values whilst high values of AST should be evaluated considering the influence of physical exercise.